2017
DOI: 10.1063/1.4997723
|View full text |Cite
|
Sign up to set email alerts
|

Removing the barrier to the calculation of activation energies: Diffusion coefficients and reorientation times in liquid water

Abstract: General approaches for directly calculating the temperature dependence of dynamical quantities from simulations at a single temperature are presented. The method is demonstrated for self-diffusion and OH reorientation in liquid water. For quantities which possess an activation energy, e.g., the diffusion coefficient and the reorientation time, the results from the direct calculation are in excellent agreement with those obtained from an Arrhenius plot. However, additional information is obtained, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 31 publications
5
41
1
Order By: Relevance
“…For n = 1, the overall jump activation energy, Eq. (19), is effectively the same as that for frame reorientation (Ea,n jump = 3.62±0.05 kcal/mol). How these two combine to predict the OH reorientation activation energy depends on the relative jump and frame timescales as given in Eq.…”
Section: Jump and Frame Contributions To Eanmentioning
confidence: 72%
See 3 more Smart Citations
“…For n = 1, the overall jump activation energy, Eq. (19), is effectively the same as that for frame reorientation (Ea,n jump = 3.62±0.05 kcal/mol). How these two combine to predict the OH reorientation activation energy depends on the relative jump and frame timescales as given in Eq.…”
Section: Jump and Frame Contributions To Eanmentioning
confidence: 72%
“…Using the calculated activation energies of the jump angle distribution, , and the characteristic jump timescale, Ea,0, the total jump contribution to the OH reorientation activation energy, Ea,n jump , can be calculated from Eq. (19). These are found to be 3.62 ± 0.05, 3.44 ± 0.05, and 3.31 ± 0.05 kcal/mol, respectively, for n = 1, 2, and 3.…”
Section: H-bond Jump Angle Distributionmentioning
confidence: 86%
See 2 more Smart Citations
“…The present work makes use of a recently developed method, derived from the application of fluctuation theory to dynamics, that has been demonstrated for calculating diffusion coefficient activation energies. [46][47][48][49] Specifically, we have previously shown that the derivative of the M SD(t) with respect to inverse temperature (β) is given by 47…”
Section: Theory Diffusion Coefficients and Activation Energiesmentioning
confidence: 99%